The Mexican Revolution : a documentary history / edited and translated, with an introduction, by Jurgen Buchenau, Timothy Henderson. - Buchenau, Jürgen, 1964-; Henderson, Timothy J. (Hackett Publishing Company, Inc., 2022)
"The Mexican Revolution is arguably the key episode in the country's modern history. The revolution became the touchstone of modern Mexican politics and culture. This volume includes key original-source documents from varying viewpoints of the revolution beginning with The Porfiriato in 1876, to the Medero Revolution in 1910, to the Huerta Interregnum (1913-1914), The War of the Factions, (1914-1915), The Early Trials of the Revolutionary Regime, 1915-1916, to The Constitutional Revolution, 1917-1920, to the period of Consolidation, 1920-1928, and finally the "Institutional Revolution," 1928-1940. A bibliography and index are included"-- Provided by publisher.
Keywords: Mexico -- History -- Revolution, 1910-1920 -- Sources.; 1910-1920; History.